The Effect of Supervision, Leadership, And Compensation on Employee Engagement in PT Prima Mas Indonesia - Hemasih, Husna; Eliyin, Eliyin; Rayuwati, Rayuwati; Yustisar, Muhamad (International Journal of Science, Technology & Management, 2022)
The research analysis aims to determine whether supervision, leadership, and compensation simultaneously have a positive and significant effect on employee engagement at PT Prima Mas Indonesia. The data analysis technique used is the associative method with the help of the SPSS version 16.0 program. This study uses multiple linear regression analysis. The sample in this study was 42 respondents. Primary data collection using a questionnaire. The results showed that partial supervision had a positive and significant effect on employee engagement at PT Prima Mas Indonesia, where tcount 2.364 > ttable 2.024 and significant 0.011 <0.05. Leadership partially has a positive and significant effect on employee engagement at PT Prima Mas Indonesia, where tcount 2,303 > ttable 2,024 and significant 0,011 < 0,05. Compensation partially has a positive and significant effect on employee engagement at PT Prima Mas Indonesia, where tcount 2.837 > ttable 2.024 and significant 0.007 <0.05. Supervision, leadership, and compensation simultaneously have a positive and significant effect on employee engagement at PT Prima Mas Indonesia, where Fcount 39.604 > Ftable 2.85 and significant 0.000 <0.05.